(untitled) (Research, Society and Development, 2020)
The National Program for the Integration of Professional Education with Basic Education in the Modality of Education of Youth and Adults (PROEJA) has an important role in Professional and Technological Education. This modality of education has historically been excluded from public policies related to the area. In this context, Education in Science, Technology and Society (STS) and Critical Mathematical Education (EMC) are shown as potential paths to integral and emancipatory formation, based on criticality, autonomy and other needs of the fundamental dimensions of life. The objective is to analyze whether the official documents of the medium level PROEJA are in compliance with the theoretical assumptions of STS and EMC Education. For this, the PROEJA Base Document for Technical Professional Education at Medium Level and also the Common National Curricular Base (BNCC) were analyzed. These documents were selected because they are both public and also because they are guidelines for all Brazilian courses in the modality. The methodology used is of a qualitative and documentary analysis. It was evidenced that both present, although not directly, STS Education in its precepts. For the EMC, it was found that only BNCC presents evidences in respect to this movement, even though it does not explicitly emphasize the approach. Several similarities were reported in the documents with what is expected from a formation based on both approaches.